Ceftolozane/Tazobactam Pharmacokinetics in a Critically Ill Adult Receiving Continuous Renal Replacement Therapy. Issue 5 (2nd May 2016) - Bremmer, Derek N.; Nicolau, David P.; Burcham, Pam; Chunduri, Anil; Shidham, Ganesh; Bauer, Karri A.
Abstract : Limited data are available on ceftolozane/tazobactam dosing in patients receiving continuous renal replacement therapy (CRRT). Thus we performed a pharmacokinetic analysis of intravenous ceftolozane/tazobactam in a critically ill patient receiving CRRT at our medical center. A 47‐year‐old critically ill man with multidrug‐resistant Pseudomonas aeruginosa pneumonia, bacteremia, and osteomyelitis was receiving ceftolozane/tazobactam 3 g (ceftolozane 2 g/tazobactam 1 g) every 8 hours while receiving continuous venovenous hemodiafiltration (CVVHDF). After the fifth dose of ceftolozane/tazobactam, plasma samples were obtained at 1‐, 2‐, 4‐, 6‐, and 8‐hour time points. Two additional post‐hemodialysis filter plasma samples were obtained to assess CVVHDF clearance. The maximum and minimum plasma concentrations for ceftolozane were 163.9 μg/ml and 79.4 μg/ml, respectively. The area under the plasma concentration–time curve from 0–8 hours (AUC0–8 ) was 689 μg hour/ml; the plasma half‐life was 13.3 hours. The ceftolozane CVVHDF clearance and total clearance were 2.4 L/hour and 2.9 L/hour, respectively. Compared with a patient with normal renal function, this patient receiving CVVHDF had decreased ceftolozane clearance. A ceftolozane/tazobactam dosage of 1.5 g every 8 hours should adequately achieve a desired drug concentration above the minimum inhibitory concentration of 8 μg/ml for the treatment of pneumonia. Additional pharmacokinetic data are needed to confirm our results and for alternative forms of CRRT.